Managing Type 2 Diabetes through Diet and Exercise: Effects on Sleep and Sexual Health in Men from Mazar-e-Sharif, Afghanistan (1398-1399) - Hekmati, Abdul Hakim; Rahimzadeh, Abdullah Darman (Journal for Research in Applied Sciences and Biotechnology, 2024)
The control of type 2 diabetes by diet, exercise and its positive effects on sleep and sexual performance of men in the conditions of Afghanistan in the city of Mazar-e-Sharif between the years 1398-1399 among 200 referring patients in private home examination and Balkh hospital of the Faculty of Medicine of the Balkh University of Afghanistan.